1983
DOI: 10.1203/00006450-198306000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Studies in the Liver and Muscle of Patients with Zellweger Syndrome

Abstract: SummaryBiochemical studies have been performed in muscle, liver, leukocytes, and fibroblasts from patients suffering from the Zellweger syndrome. Oxidation rates of [l-14Cjpyruvate, [U-14Clmalate, and [l-14C12-oxoglutarate were strongly reduced in skeletal muscle homogenate. Oxygen consumption in isolated skeletal muscle mitochondria could only be stimulated by ADP in the presence of ascorbate and N,N,N1,N1-tetramethyl-p-phenylenediamine. Cytochrome contents in heart muscle and liver mitochondria were normal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…A single enzymatic defect might explain some of these conditions; however, in the Zellweger syndrome the whole organelle would be missing, perhaps reflecting the deficit of a protein essential for the assembly of peroxisomes. Consequently, as already suggested (14,(19)(20)(21)(22)(23)(24), this pathologic condition would constitute a unique example of a genetic disorder expressed as absence of a cell organelle involved in cell metabolism.…”
mentioning
confidence: 67%
“…A single enzymatic defect might explain some of these conditions; however, in the Zellweger syndrome the whole organelle would be missing, perhaps reflecting the deficit of a protein essential for the assembly of peroxisomes. Consequently, as already suggested (14,(19)(20)(21)(22)(23)(24), this pathologic condition would constitute a unique example of a genetic disorder expressed as absence of a cell organelle involved in cell metabolism.…”
mentioning
confidence: 67%
“…Previous studies demonstrated that mitochondria are abnormal in livers of Zellweger patients and mouse Zellweger models [17][18][19][20][21][22][23] and that bile acids may mediate mitochondrial toxicity. 24 Electron microscopy demonstrated mitochondrial abnormalities typically seen in peroxisomal disorders in both early postnatal and P36 untreated PEX2 mutant livers, and these defects persisted in all BA-fed PEX2 Ϫ/Ϫ mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, steatosis and canalicular and cytoplasmic cholestasis develop with normal, deficient, or hyperplastic intrahepatic bile ducts. Another striking observation was the altered structure of mitochondria at the level of the inner membrane (5)(6)(7)(8)(9)(10). However, the precise consequences of these mitochondrial abnormalities remain largely unexplored.…”
mentioning
confidence: 99%